2018
DOI: 10.1002/2017ja025110
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Traveling Ionospheric Disturbances Generated by an Upward Propagating Gravity Wave

Abstract: Using a global atmosphere‐ionosphere coupled model, the characteristics and excitation source of traveling ionospheric disturbances (TIDs) during geomagnetically quiet periods are studied. This is the first paper concerning the simulation of TIDs generated by upward propagating gravity waves (GWs) that are spontaneously generated in the model. The dominant horizontal wavelengths of the simulated TIDs range from 700 to 1,500 km. The dominant periods and horizontal phase velocities of TIDs are 45–90 min and 250–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 43 publications
7
34
0
Order By: Relevance
“…This feature was consistent with MSTIDs in different regions (e.g., Kotake et al 2006;Otsuka et al 2011). Miyoshi et al (2018) successfully reproduced MSTIDs generated by upward propagating GWs that are spontaneously generated in the global atmosphereionosphere coupled model, and showed that the daytime MSTID was more active in winter than in summer. According to the dispersion relation for GW, the vertical wave number ( m ) of GW is expressed as where k and c are the horizontal wave number and horizontal phase speed of the gravity wave, respectively, N is the Brunt-Väisälä frequency, and H is the scale height of the neutral atmosphere.…”
Section: Phase Velocity Of Mstidssupporting
confidence: 81%
“…This feature was consistent with MSTIDs in different regions (e.g., Kotake et al 2006;Otsuka et al 2011). Miyoshi et al (2018) successfully reproduced MSTIDs generated by upward propagating GWs that are spontaneously generated in the global atmosphereionosphere coupled model, and showed that the daytime MSTID was more active in winter than in summer. According to the dispersion relation for GW, the vertical wave number ( m ) of GW is expressed as where k and c are the horizontal wave number and horizontal phase speed of the gravity wave, respectively, N is the Brunt-Väisälä frequency, and H is the scale height of the neutral atmosphere.…”
Section: Phase Velocity Of Mstidssupporting
confidence: 81%
“…However, it is not clear whether such resolutions are needed at higher levels in the thermosphere. Miyoshi et al (2018) showed that a GAIA simulation with a resolution of 1° × 1° produces fluctuations in electron density with length scales less than around 1,000 km and periods of less than around 2 hr, which are in good agreement with observations and which are not seen in a coarser resolution (2.5° × 2.5°) simulation. The fluctuations reported by Miyoshi et al are attributed to TIDs that are excited by secondary gravity waves.…”
Section: Dynamics-gravity Waves and Dynamical Formulationsupporting
confidence: 71%
“…The model needs further improvement regarding the input of solar flux. Miyoshi et al (2018) investigated the effects of the horizontal resolution on the electron density distribution using the GAIA model. They showed that fluctuations produced in model-simulated electron density with periods of less than about 2 h and length scales of less than about 1000 km with a high horizontal resolution of 1 • × 1 • , which are in good agreement with observations.…”
Section: Observed Tec Variations and Its Comparison To Tec Simulated Using Different Euv Flux Modelsmentioning
confidence: 99%